Short- and long-term outcomes of patients with minor stroke and nonvalvular atrial fibrillation - Duan, Chunmiao; Wang, Shang; Xiong, Yunyun; Gu, Hong qiu; Yang, Kaixuan; Zhao, Xing-Quan; Meng, Xia; Wang, Yongjun (BMC neurology, 2023)
Background and purpose Nonvalvular atrial fibrillation (NVAF) is a risk factor for stroke. This study was undertaken to determine the influence of NVAF on the mortality and recurrent stroke after a minor stroke event. Methods Data were derived from the Third China National Stroke Registry (CNSR-III) which enrolled 15,166 subjects during August 2015 through March 2018 in China. Patients with minor stroke (NIHSS ≤ 5) within 24 h after onset were included. Clinical outcomes including all-cause mortality, cardiovascular death, recurrent ischemic stroke, and recurrent hemorrhagic stroke were collected. The Cox proportional hazards models were used to determine the association between NVAF and clinical outcomes. Results A total of 4,753 patients were included in our study. Of them, 222 patients had NVAF (4.7%) (mean age, 71.1 years) and 4,531 patients were without AF (95.3%) (mean age, 61.4 years). NVAF was associated with 12-month cardiovascular mortality in both univariate (hazards ratio [HR], 4.13; 95% confidence interval [CI], 1.84 to 9.31; P < 0.001) and multivariate analyses (HR, 4.66; 95% CI, 1.79 to 12.15; P = 0.001). There was no difference in the in-hospital ischemic stroke recurrence rate between the two groups (HR, 0.45 [95% CI, 0.19 to 1.05] P = 0.07 at discharge). However, patients with NVAF had a lower rate of recurrent ischemic stroke at medium- (3 months and 6 months) and long-term (12 months) follow-up (HR, 0.33 [95% CI, 0.16 to 0.68] P = 0.003 at 3 months; 0.49 [95% CI, 0.27 to 0.89] P = 0.02 at 6 months; 0.55 [95% CI, 0.32 to 0.94] P = 0.03 at 12 months, respectively) compared with those without. There was no difference in all-cause mortality and hemorrhagic stroke between the two groups during follow-up. Conclusions Minor stroke patients with NVAF were at higher risk of cardiovascular death but had a lower rate of recurrent ischemic stroke compared to those without during the subsequent year after stroke event. A more accurate stroke risk prediction model for NVAF is warranted for optimal patient care strategies.